PROLOG KITAB AMSAL SEBAGAI LANDASAN PENGEMBANGAN KURIKULUM DI PERGURUAN TINGGI KRISTEN - Paulus Dimas Prabowo (The Way: Jurnal Teologi dan Kependidikan, 2023)
The background to writing this article is the condition of education in Indonesia, including Christian universities, which in practice prioritizes only intellectuality. Even though the curriculum design has been prepared with comprehensive objectives, the facts prove that intellectuals occupy the golden seat in the world of education. Increasing intelligence without being balanced with spirituality, morality and practical skills will bring more harm than benefit. Therefore, this article aims to introduce the principles of curriculum development in Christian universities taken from the prologue of the Book of Proverbs, namely 1:1-7. Proverbs are suitable as a biblical basis for curriculum development because this book was originally used to instruct and educate young people in ancient Israel. The method used is literature study and exegetical analysis. As a result, the Prologue of Proverbs contains spiritual, intellectual, moral-social and practical aspects (problem solving), and it can be concluded that curriculum development in Christian universities needs to touch on these aspects.